Kinetic changes of gait initiation in individuals with chronic ankle instability: A systematic review - Marzieh Mortezanejad; Aliyeh Daryabor; Zahra Ebrahimabadi; Abbas Rahimi; Mohammad Yousefi; Fatemeh Ehsani; Ali Maleki (Health Science Reports)
Abstract Background and Aims Gait initiation (GI) in individuals with chronic ankle instability (CAI) has shown differences in the center of pressure (COP) and muscular measures compared to healthy controls. Some studies reported that these alterations appeared when GI was with the affected leg, while others indicated that they occurred when GI was with the non‐affected leg. This systematic review aimed to understand kinetic and muscular differences between individuals with CAI, healthy controls, and the affected and non‐affected legs of individuals with CAI. Methods PubMed, Science Direct, Web of Science, Google Scholar, and Scopus databases (1990–2023) were searched using the Population, Exposure, Comparator, and Outcome measure. The PRISMA guidelines were followed. The outcome measures were the peak and rate of COP displacement in the medial‐lateral and anterior‐posterior directions, and resultant plane during phases 1, 2, and 3 of COP trace during GI and the duration of each phase. The other measures included the onset time of the tibialis anterior and soleus muscle activity between individuals with CAI, healthy controls, and the affected and non‐affected legs of the individuals with CAI. The studies' quality assessment was conducted based on the Strengthening the Reporting of Observational Studies in Epidemiology checklist. Results Five studies were included in the final evaluation. The results of included studies showed, individuals with CAI spent less time during phases 1 and 2, as well as a shorter peak of COP displacement in the lateral direction during phase 1 compared to healthy controls, regardless of whether the GI was with the affected or non‐affected leg. Conclusion Individuals with CAI have probably adopted a strategy involving adjusting the peak of COP displacement to manage internal sway while in a single‐leg stance. Overall, there was no comprehensive conclusion about differences between the two legs in individuals with CAI.